Insular cortex activity during food-specific inhibitory control is associated with academic achievement in children - Menna Price (Physiology and Behavior, 2022)
Background/objectives: Inhibitory control (IC) is usually poorer in children with overweight and obesity and has been associated with unhealthy eating behaviors and lower academic achievement. Food-specific IC tasks depicting salient unhealthy foods may be more sensitive to predicting fat accumulation and unhealthy behaviors than traditional IC tasks. However, the neural activation patterns in response to food-specific IC remain unclear, especially in developing children`s brains. Here, we investigated brain activity associated with food-specific IC in children with accumulated fat mass. Subjects/Methods: 36 children with overweight and obesity performed a food-specific Go/No-Go task in an MRI scanner. We assessed the children’s body composition with dual-energy x-ray absorptiometry, academic achievement, somatic maturation, and cardiorespiratory fitness. Results: The left insular cortex was significantly activated during successful inhibition of palatable food cues and was associated with higher academic achievement. Also, linear regression showed that academic achievement correlated with insular cortex activation even when controlling for somatic maturation, cognitive performance, and cardiorespiratory fitness. Conclusion: Our results indicate that insular cortex activation, an area known for rational and emotional processing, is associated with successful inhibitory control in response to food images in children with overweight and obesity, while academic performance seems to play a role in the magnitude of this activation.